A general theory of rock glacier creep based on in‐situ and remote sensing observations. (4th December 2020) - Cicoira, Alessandro; Marcer, Marco; Gärtner‐Roer, Isabelle; Bodin, Xavier; Arenson, Lukas U.; Vieli, Andreas
Abstract: The ongoing acceleration in rock glacier velocities concurrent with increasing air temperatures, and the widespread onset of rock glacier destabilization have reinforced the interest in rock glacier dynamics and in its coupling to the climate system. Despite the increasing number of studies investigating this phenomenon, our knowledge of both the fundamental mechanisms controlling rock glacier dynamics, and their long‐term behaviour at the regional scale remain limited. We present a general theory to investigate rock glacier dynamics, its spatial patterns and temporal trends at both regional and local scale. To this end, we combine a model to calculate rock glacier thickness with an empirical creep model for ice‐rich debris, in order to derive the Bulk Creep Factor (BCF), which allows to disentangle the two contributions to the surface velocities from (i) material properties and (ii) geometry. Thereafter, we provide two examples of possible applications of this approach at a regional and local scale.